Application of Raw Material Inventories Using the ABC Class Classification Method and the EOQ Method in Raw Material Inventories Based on POM QM For Windows: (Case Study on Surabi Gapura Purwakarta 2023) - Dewi Puspasari; Yus Djunaedi Rusli (Transformasi: Journal of Economics and Business Management, 2023)
The quality of a product depends on how the manufacturer applies the supply of raw materials used. The application of a good supply of raw materials can expedite the production process. There are many factors that affect the smooth production process. One of the factors that can affect the smoothness of the production process is the supply of raw materials. Raw materials in the production process include raw materials, semi-finished materials and finished goods. In running its business, Kedai Surabi Gapura experiences difficulties in terms of implementing raw material supplies considering the large number of orders that the shop receives every month so that Kedai Surabi Gapura cannot determine the number of priority raw material needs that must be purchased according to production needs. Surabi Gapura requires an appropriate method of supplying raw materials for production. By applying the raw material inventory classification method, it is hoped that Kedai Surabi can find out the priority classification of raw materials used based on raw material prices, in this case related to capital. Shop owners need to implement raw material inventory planning and control because to find out what the difference is between the costs incurred for purchasing raw materials and the amount of raw material requirements according to the daily production target. In addition to the raw material inventory classification method needed in an effort to expedite the production process, the shop also needs to apply the right raw material ordering method in order to save costs incurred such as transportation costs for sending raw materials, raw material storage costs, ordering costs, raw material maintenance costs arising from inventory. By applying the EOQ method for reordering raw materials, it is hoped that the Surabi Gapura Shop will place orders in economical quantities to determine the point of reordering raw materials so that the costs incurred by the Surabi Gapura Shop are efficient.The research method used in this study is to use a quantitative descriptive method. In this study the method used aims to determine the appropriate method of inventory of production raw materials with the raw material inventory classification method and the correct raw material ordering method in order to save costs incurred such as transportation costs for sending raw materials, raw material storage costs, ordering costs, maintenance costs for raw materials arising from inventory. By applying the EOQ method for reordering raw materials.From the results of calculations using the POM QM For Windows software based on the results of data processing using the ABC class classification analysis method for raw materials from 15 types of raw materials, they can be classified based on their respective classes according to the amount and investment value or rupiah spent to obtain these raw materials. Then by using the calculation of the EOQ method with the POM QM For Windows software, business owners can find out the optimal number of orders in the production process, namely the optimal number of orders is at 8,869.52 units, that is, if the demand in one day is 250 units.